Rationale and study design of ARCHER: a randomized, double-blind, Phase III study of dacomitinib versus erlotinib for advanced non-small-cell lung cancer. (January 2013) - Boyer, Michael; Jänne, Pasi Antero; Mok, Tony; O'Byrne, Kenneth; Paz-Ares, Luis; Ramalingam, Suresh S; Liang, Jane; Taylor, Ian; Campbell, Alicyn; O'Connell, Joseph; Letrent, Stephen; Antic, Vladan
Background: Dacomitinib (PF-00299804) is an irreversible pan-HER tyrosine kinase inhibitor. We describe the rationale and design of a Phase III, randomized, double-blind study of dacomitinib versus erlotinib in patients with advanced non-small-cell lung cancer (NSCLC) following one or two prior lines of therapy in the advanced setting.Method: The primary end point of the study is progression-free survival per independent radiologic review in two co-primary patient populations: all patients with NSCLC (∼800) and patients with confirmed KRAS wild-type NSCLC (at least 400). The study is powered to detect ≥33 and 45% improvement in progression-free survival in all NSCLC and KRAS wild-type NSCLC, respectively. The sample size will allow assessment of difference in overall survival in the co-primary populations with adequate power (i.e., ≥80%).